Collaborative governance of Narsalis larvatus (Wurmb, 1787) conservation in Barito Kuala Regency, Indonesia - Fajrina, Amaliana Nur; Hijri, Yana S; Roziqin, Ali; Rezeki, Amalia (Ecological Questions, 2022)
Natural resources and social conflict have a strong relationship. The current natural resource management problems have caused deforestation, resulting in unstable environmental ecosystems. Consequently, a movement towards mitigating natural resource management emerged because of the threat to the “Bekantan” Proboscis Monkey habitat and population in South Kalimantan Province. Indonesian Proboscis Monkey Friends (SBI) Foundation is a non-profit organization aiming to protect Proboscis monkeys on Curiak Island. SBI adopts collaborative resource governance in building stakeholder capacity with shared motivation and principles for collective action. Therefore, this study aimed to describe the collaborative governance process conducted on Proboscis Monkey conservation in Curiak Island. The results showed that anyone, including non-government organizations, could initiate collaboration in the several programs such as conservation, buy back the land and rambai mangrove restoration. Various parties collaborations are proven to successfully increase the support for environmental conservation efforts, especially the habitat and endemic proboscis monkeys.